2017
DOI: 10.1021/acs.molpharmaceut.7b00521
|View full text |Cite
|
Sign up to set email alerts
|

Design and Solidification of Fast-Releasing Clofazimine Nanoparticles for Treatment of Cryptosporidiosis

Abstract: Clofazimine, a lipophilic (log P = 7.66) riminophenazine antibiotic approved by the US Food and Drug Administration (FDA) with a good safety record, was recently identified as a lead hit for cryptosporidiosis through a high-throughput phenotypic screen. Cryptosporidiosis requires fast-acting treatment as it leads to severe symptoms which, if untreated, result in morbidity for infants and small children. Consequently, a fast-releasing oral formulation of clofazimine in a water-dispersible form for pediatric adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 46 publications
2
73
0
Order By: Relevance
“…Compared to previously reported efficiency entrapment values for other formulations, similar values were obtained for DAP loaded in surfacefunctionalized solid lipid nanoparticles based on cetyl palmitate [12], but lower than those reported for theospheres [9]. Concerning CLZ, better entrapment efficiency was reported for more hydrophobic formulations, based on hypromellose acetate succinate, lecithin, and zein [13]. This is expected, considering the hydrophobic character of CLZ.…”
Section: Application To Evaluation Of Nanoformulationssupporting
confidence: 82%
“…Compared to previously reported efficiency entrapment values for other formulations, similar values were obtained for DAP loaded in surfacefunctionalized solid lipid nanoparticles based on cetyl palmitate [12], but lower than those reported for theospheres [9]. Concerning CLZ, better entrapment efficiency was reported for more hydrophobic formulations, based on hypromellose acetate succinate, lecithin, and zein [13]. This is expected, considering the hydrophobic character of CLZ.…”
Section: Application To Evaluation Of Nanoformulationssupporting
confidence: 82%
“…For instance, their extremely large surface area to volume ratio accounts for their significantly higher saturation solubility and dissolution rate compared to their coarse counterparts. This unique characteristic has been successfully exploited in the solubility enhancement of poorly water-soluble drugs (Zhang et al, 2017). Specifically, drug-loaded polymeric nanoparticles with particle size below 200 nm have been shown capable of crossing biological barriers (Fernandes et al, 2010), mitigating first-pass hepatic metabolism (Italia et al, 2007) and displaying enhanced permeability and retention (EPR) effect (Allen and Cullis, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of its high efficiency and excellent reproducibility, FNP has been successfully applied to the production of stable nanoparticles for only a limited number of highly hydrophobic compounds or drugs including beta-carotene (Zhu et al, 2010), paclitaxel (Saad, 2007) and bifenthrin (Liu et al, 2008b). To ensure good nanoparticle stability, it has been suggested that the compound involved must have a log P value of over 6 (Zhang et al, 2017;Zhu, 2014). However, drugs typically have log P values between 3 and 6, which inevitably raise serious instability issue when they are prepared as nanoparticles by FNP.…”
Section: Introductionmentioning
confidence: 99%
“…These formulations are intended to provide access points for learning the process and consequently use non-degradable poly(styrene)-based polymers. Alternative stabilizers have been described in the literature, with a number of biocompatible commercial options available 14,23,24 .…”
mentioning
confidence: 99%